INCREASING MSMEs SALES THROUGH DETERMINING COST OF GOODS SOLD (COGS) AND DIGITAL MARKETING - Firmandani, Wahyu; Sophia, Elsha; Eriani, Izmi Dwira; Ardelia, Belva Abidah; Yahya, Adrian (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
MSMEs have an important role in a nation's economy because of their contribution to national sales and employment. Moreover, the structure of business entities in Indonesia is still dominated by small and medium-sized enterprises (SMEs). Small- and medium-sized enterprises (SMEs) are compelled to compete on the global market due to the numerous blows from global competition and the prospect of recession. To increase the competitiveness of domestic MSMEs so that they can excel on the international stage, strategic and effective methods are required, such as implementing the marketing mix. Community service through a marketing mix strategy aims to increase MSMEs in Gresik Regency's comprehension of how to implement marketing mix strategies in order to prepare themselves for entry into the global market, which will result in increased sales. The method is implemented in three stages from March to October 2023: the preparation stage, the implementation stage, and the evaluation stage. The preparatory phase commences with routine coordination with partners and condition analysis. The implementation phase is subsequently executed via training, mentoring, question-and-answer sessions, and case discussions. In the evaluation phase, a pre-test, post-test, question-and-answer session, and questionnaire are utilized. Target partners are actively involved at all stages, so that the output targets can be achieved well. The implementation has resulted in an increase in MSMEs' knowledge of the marketing mix, which includes product, place, promotion, and price, as well as an increase in MSMEs' sales due to their increased global marketing reach. This community service also contribute to the achievement of Sustainable Development Goals 8 (Decent Work and Economic Growth) and 9 (Industry, Innovation, and Infrastructure).